1978
DOI: 10.1021/j100513a006
|View full text |Cite
|
Sign up to set email alerts
|

Study of metal oxide catalysts by temperature programmed desorption. 4. Oxygen adsorption on various metal oxides

Abstract: Oxygen adsorption properties of 16 metal oxides were investigated by means of a temperature programmed desorption (TPD) technique. Although oxygen adsorption phenomena were largely different depending on metal oxides, it was possible to classify the oxides as follows: (A) V205, MoOa, Bi203, W03, and 203•2 03 which exhibit no oxygen desorption over the range 10-560 °C; (B) Cr203, Mn02, Fe203, Co304, NiO, and CuO which always give relatively large amounts of oxygen desorption; and (C) Ti02, ZnO, Sn02, A1203, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
156
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(168 citation statements)
references
References 11 publications
9
156
0
Order By: Relevance
“…Much effort has been made to correlate the results of the TPD studies on SnO 2 [84,85,[92][93][94][95] with the changes in electrical conductivity, and assign observed TPD peaks to different oxygen species using EPR spectroscopy. In several works, TPD was done in combination with/in parallel to 1) EPR and electrical conductivity, [84] 2) EPR, [93] 3) DC conductance (on thick film samples) and CPD (on films), [95] 4) electrical conductivity.…”
Section: Temperature Programmed Desorptionmentioning
confidence: 99%
“…Much effort has been made to correlate the results of the TPD studies on SnO 2 [84,85,[92][93][94][95] with the changes in electrical conductivity, and assign observed TPD peaks to different oxygen species using EPR spectroscopy. In several works, TPD was done in combination with/in parallel to 1) EPR and electrical conductivity, [84] 2) EPR, [93] 3) DC conductance (on thick film samples) and CPD (on films), [95] 4) electrical conductivity.…”
Section: Temperature Programmed Desorptionmentioning
confidence: 99%
“…The treatment demonstrates the usefulness of linear free energy relationships, which are state of the art for organic solution chemistry, for inorganic solid-state reactions. (10) and (11). The decomposition of DH °i nto contributions from DH°V and DH 0 ox is based on Equation (14).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[11] Oxygen permeation measurements under surface limited conditions yield a reaction order of [13] ), which indicates that only atomic oxygen species are involved in the rate determining step. The relationship in Equation (2) between the effective activation energies of k * and D* and the mechanism of the diffusion process resulting in Equation (9) imply a significant contribution b DH°V to the effective activation energy E k* of the surface reaction, which stems from the V CC O jump activation enthalpy.…”
mentioning
confidence: 99%
“…By oxygen-TPD technique, investigation of the oxygen uptake of 16 metal oxides including the first row transition metal oxides has been reported [45,46]. The authors found that the transition metal oxides always gave relatively large amounts of oxygen desorption even at high temperatures.…”
Section: Discussionmentioning
confidence: 99%